Algorithmic Dispute Resolution—The Automation of Professional Dispute Resolution Using AI and Blockchain Technologies. (9th November 2017) - Barnett, Jeremy; Treleaven, Philip
Abstract: Legal Services industries are entering a period of major disruption caused by new legal technologies (LawTech), such as artificial intelligence (AI), Internet of Things (IoT) and Blockchain. An area already undergoing major innovation is alternative dispute resolution (Alternative Dispute Resolution (2017) Wikipedia, https://en.wikipedia.org/wiki/Alternative_dispute_resolution ), especially automated online dispute resolution (Online Dispute Resolution (2017) Wikipedia, https://en.wikipedia.org/wiki/Online_dispute_resolution ; Katsh, E. and Rifkin, J. (2001) Online Dispute Resolution: Resolving Conflicts in Cyberspace. Jossey-Bass Wiley, New Jersey). In terms of LawTech, we broadly divide online dispute resolution into (a) Consumer ODR —uses technology to facilitate the resolution of disputes between ecommerce parties, typically online suppliers and consumers; (b) Judicial ODR —covers any means of settling 'ordinary' disputes where there is a hearing (using technology) but outside of the courtroom, such as divorce or personal injury cases; and what we refer to as (c) Corporate ODR —the use of technology to manage the resolution of any contractual disputes that may emerge from major multi-partner projects or financial transactions. This paper focuses on ODR and specifically the future use of automating anticipatory Corporate dispute resolution using AI and blockchain technologies. The paper describes the legal sector, and how it is being radically transformed by computer science.